Together towards campus digitization - Mimi Rabita, Abdul Wahit (2020)
Pekan, 6 November 2020 - Universities need to make comprehensive preparations in the era of the digital revolution to remain competitive and accelerate progress as well as shape the glory in the national education landscape.